Comparison on the vision‐related quality of life between outpatients and general population with dry eye syndrome. (31st July 2013) - Le, Qihua; Ge, Ling; Li, Meiyan; Wu, Liangcheng; Xu, Jianjiang; Hong, Jiaxu; Gong, Lan
Abstract. Purpose: To compare the impact of dry eye syndrome (DES) on vision‐related quality of life (VR‐QoL) between outpatients and general populations. Methods: This cross‐sectional comparative study enrolled 154 participants, 77 outpatients and 77 general participants, all of whom met the diagnostic criteria of DES. Apart from the collection of sociodemographic and clinical data, the Chinese version of 25‐item National Eye Institute Visual Functioning Questionnaire (NEI VFQ‐25) and Ocular Surface Disease Index Questionnaire (OSDI) were administered. Main outcome measures include the comparison on the OSDI score and VFQ‐25 score between two groups, and their correlation with sociodemographic and clinical data. Results: The two groups were comparable concerning sociodemographic parameters except that the outpatients were better educated (χ2 = 18.609, p < 0.001). The ophthalmic data related with DES did not have statistically significant differences between two groups except that the proportion of subjects with positive corneal fluorescein staining (CFS) was higher in outpatients (χ2 = 21.296, p < 0.001). The outpatients reported significantly higher OSDI scores and lower VFQ‐25 scores. The VFQ‐25 composite score had negative correlation with the OSDI score of all participants or that of outpatients solely (ρ = −0.247 and −0.397, p = 0.030 and 0.000, respectively). Among outpatients, the value of Schirmer test (ST), tear film breakup time (TBUT) and CFS in the eyes with worse DES had significant correlations with the OSDI overall scores, while TBUT and CFS of both eyes correlated with the VFQ‐25 composite score. Conclusions: DES exerts more adverse impact on VR‐QoL in outpatients than general patients. The impairment of VR‐QoL has a significant correlation with the severity of DES.